A-FABP Concentration Is More Strongly Associated with Cardiometabolic Risk Factors and the Occurrence of Metabolic Syndrome in Premenopausal Than in Postmenopausal Middle-Aged Women. (29th May 2014) - Stefanska, Anna; Ponikowska, Irena; Sypniewska, Grazyna
Abstract : We aimed at the evaluation of the relationship between adipocyte fatty acid binding protein (A-FABP) and cardiometabolic risk factors in premenopausal and postmenopausal women. Additionally, we compared A-FABP with adipokines related to metabolic syndrome (MetS) such as leptin and adiponectin. 94 premenopausal and 90 early postmenopausal middle-aged Caucasian women were subject to examinations. Postmenopausal women had higher A-FABP than premenopausal; this difference became insignificant after controlling for age. We found significantly higher correlation coefficients between A-FABP and TC/HDL-C ratio and number of MetS components in premenopausal women, compared to postmenopausal. Each 1 ng/dL increase in A-FABP concentration significantly increased the probability of occurrence of atherogenic lipid profile in premenopausal women, even after multivariate adjustment. All odds ratios became insignificant after controlling for BMI in postmenopausal women. A-FABP was more strongly associated with MetS than leptin and adiponectin in premenopausal women. Adiponectin concentration was a better biomarker for MetS after menopause. Our results suggest that the A-FABP is more strongly associated with some cardiometabolic risk factors in premenopausal than in postmenopausal women. Higher values of A-FABP after menopause are mainly explained by the fact that postmenopausal women are older. Because of the limitation of study, these results should be interpreted with caution.